Productivity and Productivity Information: Towards Optimizing and Balancing Organizational Efficiency and Effectiveness - Tested in the Agricultural Sector - Abdalla, Abdalla Khidir; Mansour, Ilham Hassan; Eljelly, Abuzar Mohamed; Abdalla, Yousif Abdelbagi (Gezira Journal of Economic and Social Sciences; مجلد 13 عدد 1 (2022), 2022)
Abstract The pressure for information on how a corporation creates value over time to benefit stakeholders is mounting since the 2008 financial crises. The COVID-19 pandemic social and economic impacts and consequences will inevitably force many corporations to report how the available resources are efficiently and effectively utilized. Hence, reflect how the organization's growth and profitability are sustainable. This study attempts to introduce and examine a systematic and integrated productivity-based framework for developing appropriate performance management systems that help resolve the dilemma of central business terms: organizational efficiency and effectiveness. The study builds on productivity, activity-based management, and resources concepts using mathematical and qualitative analytical methods for conceptualization. The study concludes the importance of "Productivity Information" integrated with activity-based management for balancing organizational efficiency and effectiveness. Besides, the study establishes that productivity is superior to all conventional financial measures, and it is the driving force of real business results and outcomes. Moreover,  the study shows that "Productivity Information" would help in preparing integrated and sustainability reports. The framework foundations are developed and tested in the context of the agricultural sector. The study calls for further studies to explore the richness of productivity information in enhancing business excellence and performance. A call is also made for developing a new breed of professionals around the productivity involving multi-disciplinary and multi-sectoral professions from the various fields of knowledge.